STUDENT TEACHER’S ATTITUDE TOWARDS ONLINE LEARNING DURING COVID-19 - Dr.K.Nachimuthu* (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to determine the attitude towards online learning by the student teachers in the Covid-19 Period. In this research, the Survey type of tool used as google forms. Online learning supported instruction is an independent variable and student attitudes towards online learning through computers are dependent variables. As a data collection instrument used is an online learning attitude scale and the sample consists of 130 student teachers. According to analysis concludes, normal classroom practice does not affect attitudes of students towards online learning and there is no significant difference between the male and female attitude scores of student teachers toward online learning practice in Covid-19.